已知f(1+sinx)=2+sinx+cos2x,求f(x)令u=1+sinx,则sinx=u-1 (0≤u≤2),则f(u)=-u2+3u+1 (0≤u≤2)故f(x)=-x2+3x+1 (0≤u≤2)【f(u)=-u2+3u+1】是怎么得来的?求教!

来源:学生作业帮助网 编辑:作业帮 时间:2024/05/13 20:12:05

已知f(1+sinx)=2+sinx+cos2x,求f(x)令u=1+sinx,则sinx=u-1 (0≤u≤2),则f(u)=-u2+3u+1 (0≤u≤2)故f(x)=-x2+3x+1 (0≤u≤2)【f(u)=-u2+3u+1】是怎么得来的?求教!
已知f(1+sinx)=2+sinx+cos2x,求f(x)
令u=1+sinx,则sinx=u-1 (0≤u≤2),则f(u)=-u2+3u+1 (0≤u≤2)
故f(x)=-x2+3x+1 (0≤u≤2)
【f(u)=-u2+3u+1】是怎么得来的?
求教!

已知f(1+sinx)=2+sinx+cos2x,求f(x)令u=1+sinx,则sinx=u-1 (0≤u≤2),则f(u)=-u2+3u+1 (0≤u≤2)故f(x)=-x2+3x+1 (0≤u≤2)【f(u)=-u2+3u+1】是怎么得来的?求教!
f(1+sinx)=2+sinx+cos²x
cos²x=1-sin²x=1-(u-1)²=1-u²+2u-1=-u²+2u
f(u)=2+(u-1 )+(-u2+2u) (0≤u≤2)
=2+u-1--u2+2u
=-u²+3u+1
故f(x)=-x²+3x+1 (0≤x≤2)

原式中cos2X=1-2sin∧2X,再把这个用U代出来就可以了